KEMAMPUAN MENULIS EKSPOSISI PROSES PADA SISWA KELAS IV B SD BAPTIS PALEMBANG - Leonardus Hendra Kristanto (Universitas Katolik Musi Charitas, 2023)
Writing is one of the basic language skills that humans must possess in addition to listening, speaking, and reading. In general, exposition texts are divided into 6 types, namely definition exposition, classification exposition, illustration exposition, comparison exposition, report exposition and process exposition. In this study, the focus is on examining process exposition, namely explanations or written steps to explain how something happens. The formulation of the problem in this study is how the ability to write process exposition in fourth grade students of SD Baptist Palembang. The triangulation technique used by the researcher is the researcher's triangulation by giving the students' writings to the validator to be checked so that the data used by the researcher is truly valid. The data validity technique used triangulation of sources and methods. This study aims to determine the ability of the process exposition of fourth grade students of SD Baptist Palembang. Data collection techniques are by observation, interviews, and tests. The subjects in this study were grade IV students, totaling 23 students. The results of this study are: Students who get a score of 66.66 as much as 4% (1 student), a score of 75 as much as 23% (5 students), a score of 77.77 as much as 4% (1 student), a score of 83.33 as much as 14% (3 students), the value of 91.66 is 32% (7 students), the value of 100 is 23% (5 students). So from 23 students who got a score of 75 as many as 17 students.